2015
DOI: 10.1136/bcr-2015-211383
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resolution of a recurrent axillary cystic hygroma following acute infection

Abstract: We report a case of spontaneous resolution of a recurrent axillary cystic hygroma in a 4-year-old boy. He presented with a 1-year history of a cystic lump in the left axilla, which intermittently changed in size. Ultrasound suggested it was a lipoma, with raised suspicions of vascular malformation. Scans were discussed in a multidisciplinary meeting and provisional diagnosis of lymphocele or slow flow lymphovascular malformation was made. It was surgically excised and histology confirmed the lesion to be a cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…This was like earlier studies where the author stated that both genders were equally affected. 11,12 In this study, the most frequent site of LMs was neck (78%) followed by another site like cheek, chest, shoulder, and suprapubic region. Various other studies also reported neck as the most frequent site for LMs in different proportion (40-60%).…”
Section: Discussionmentioning
confidence: 58%
“…This was like earlier studies where the author stated that both genders were equally affected. 11,12 In this study, the most frequent site of LMs was neck (78%) followed by another site like cheek, chest, shoulder, and suprapubic region. Various other studies also reported neck as the most frequent site for LMs in different proportion (40-60%).…”
Section: Discussionmentioning
confidence: 58%
“…Drainage and antibiotics were recommended in several reports. 4 However, effective tube drainage was prevented by the highly viscous contents and septa in the cyst. Hence, these components had to be removed effectively and noninvasively.…”
Section: Discussionmentioning
confidence: 99%